2019
DOI: 10.1149/09101.1009ecst
|View full text |Cite
|
Sign up to set email alerts
|

Leakage Current and Chemical Potential Profile in Proton-Conducting Bi-Layered Solid Oxide Electrolyte with BZY and Hole-Blocking Layers

Abstract: Solid oxide fuel cells (SOFCs) with proton-conducting solid electrolyte, instead of the oxide-ion conducting solid electrolyte have attracted attentions because of their high potential to reduce operating temperatures and to enhance the electrical efficiencies of SOFCs. In addition, the proton-conducting SOFCs with multistage electrochemical oxidation configuration will be promising technology for critically-high electric efficiencies. However, it is known that there are non-negligible charge -carriers other t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Although BZY is used as the electrolyte material in this study, the model framework is also applicable to mixed-conducting ceramic fuel cells and electrolytic cells with other electrolyte materials, such as SrCe 1− x Yb x O 3 , 19 SrZr 1− x Y x O 3− δ 40 and La 28− x W 4+ x O 54+ δ . 41 There are also multiple defect transport phenomena in these materials. Moreover, although hydrogen is used as fuel in this paper, the model can also be further developed to study other H-SOFCs fueled by hydrocarbons and ammonia.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…Although BZY is used as the electrolyte material in this study, the model framework is also applicable to mixed-conducting ceramic fuel cells and electrolytic cells with other electrolyte materials, such as SrCe 1− x Yb x O 3 , 19 SrZr 1− x Y x O 3− δ 40 and La 28− x W 4+ x O 54+ δ . 41 There are also multiple defect transport phenomena in these materials. Moreover, although hydrogen is used as fuel in this paper, the model can also be further developed to study other H-SOFCs fueled by hydrocarbons and ammonia.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…[21][22][23] Unlike perovskite-type oxides, alkali-proton-exchanged oxides suffer less from electronic current leakage under high oxygen potentials because the proton is incorporated by ion exchange, not by the hydration of oxygen vacancies introduced by acceptors. 24,25 The alkali-proton exchange technique provides an outstanding possibility for producing a wide variety of proton-conducting oxides with a skeleton of excellent alkali-ion conductors, some of which may show high proton conductivities at intermediate temperatures with reasonable chemical stability.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, lanthanum tungstate, La28-xW4+xO54+3x/2v2-3x/2 with a La/W ratio of 6.7 (LWO) was successfully used as a hole-blocking layer in a bilayer electrolyte to suppress leakage current (1)(2)(3). Additionally, it was shown that a bilayer electrolyte, made of BaZr0.8Yb0.2O3−δ (BZYb) and BaZr0.1Ce0.7Y0.1Yb0.1O3−δ (BZCYYb), can reduce the interfacial resistance between the cathode and the electrolyte and can also prevent nickel diffusion from the anode due to high-temperature cell fabrication processing (4).…”
Section: Introductionmentioning
confidence: 99%